Impact of Methionine Synthase Gene and Methylenetetrahydrofolate Reductase Gene Polymorphisms on the Risk of Sudden Sensorineural Hearing Loss - Gross, Menachem; Friedman, Gideon; Eliashar, Ron; Koren-Morag, Nira; Goldschmidt, Neta; Atta, Iman Abou; Ben-Yehuda, Arie (Audiology & neurotology, 2006)
Idiopathic sudden sensorineural hearing loss (SSNHL) represents a frequently encountered otological disease of unknown etiology. In recent years, several inherited risk factors have been found in the pathogenesis of vascular diseases. In the present study, we determined whether specific polymorphism or the combination of polymorphisms in folate-dependent homocysteine metabolism genes can act as predisposing inherited vascular risk factors in the development of SSNHL. We conducted a prospective case-control study using DNA samples extracted from 81 patients diagnosed as suffering from SSNHL and 264 healthy control subjects. Three functional polymorphisms were analyzed by polymerase chain reaction amplification, restriction enzyme digestion, and DNA fragment separation by electrophoresis: methylenetetrahydrofolate reductase (MTHFR) C677T, MTHFR A1298C, and methionine synthase (MTR) A2756G polymorphisms. The prevalence of the homozygous genotype of MTR 2756GG in the SSNHL patients (9%) was significantly higher than in the control group (4%) (p = 0.011). The allelic frequency of the G allele of the MTR A2756G polymorphism among SSNHL patients (12.5%) was also significantly higher than in the control group (5%) (p = 0.033). The prevalence of patients possessing two polymorphisms (31%) and three polymorphisms (17%) in the SSNHL group was significantly higher than in the control group (23 and 9%, respectively; p = 0.019). The frequency of patients with a very high rank risk (double homozygous) was significantly higher in the SSNHL group, MTHFR 677TT/MTR 2675GG – 7%, than the frequency of patients in the control group, MTHFR 677TT/MTR 2675GG – 3% (p = 0.030). Certain polymorphisms in genes encoding enzymes in the folate-dependent homocysteine metabolism are associated with SSNHL. In our case-control study, a significant association between MTR 2756GG genotype and SSNHL was found which may represent an inherited vascular risk factor in the pathogenesis of SSNHL.